Smartphones, artificial intelligence and digital histopathology take on basal cell carcinoma diagnosis. (19th August 2019) - Lee, K.J.; Soyer, H.P.
Abstract : Linked Article : Jiang et al. Br J Dermatol 2020;182: 754–762 .